Capacity Citizen's Participation of the People Users of Marihuana in Bogotá - Colombia - Triana-Velázquez, Oscar David (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article intends to investigate the way in which recreational marijuana users, who live in the city of Bogotá, exercise their right to citizen participation, demonstrating against the prohibition of said substance. For this, a case study of the collective "Yes to the personal dose" of the District University was carried out, in the framework of which interviews were conducted with activists of said group, and the participant observation in the Colombian cannabis carnival, which is the most visible event of those where these citizens demonstrate against the prohibition of marijuana. An educational, flexible and participatory approach was proposed as the most effective, in relation to the prohibitionist model in force so far in Colombia. The voices of two activists bring us closer to their arguments and their practices of social organization.